Governance Community Empowerment Through the EMAK.ID Waste Bank Program in Bandar Lampung City - Irawansyah, Aditiya; Puspawati, Ani Agus; Prihantika, Ita (Journal Governance Bureaucratic Review, 2025)
Waste management is one of the most urgent environmental problems in Indonesia, especially in urban centers like Bandar Lampung City, where waste generation has risen to over 870 tons per day, putting pressure on landfills and creating serious environmental and health risks. Conventional disposal approaches have proven insufficient, prompting the introduction of the Emak.ID Waste Bank program as a community-based solution that combines waste reduction with empowerment. The purpose of this study is to analyze how the program fosters empowerment across four key dimensions Awakening, Understanding, Harnessing, and Using—while assessing its role in strengthening community participation in sustainable waste management. This research employed a qualitative descriptive design, using in-depth interviews, observations, and document analysis centered on the Gunter community group, which has successfully practiced independent weighing since late 2022. The findings show that the program improved waste segregation, enhanced environmental literacy, and provided modest financial incentives from recyclables, while also fostering social cohesion through regular training and collective weighing activities. However, participation remains inconsistent due to low environmental literacy, competing daily priorities, and limited economic returns. Despite these challenges, the Emak.ID model demonstrates how waste banks can operate not only as environmental interventions but also as platforms for community empowerment and micro-entrepreneurship. The study concludes that for long-term sustainability, waste bank initiatives require stronger integration of educational, economic, and institutional support. This case highlights the potential of participatory waste governance as a replicable model for advancing sustainable urban development and circular economy practices in Indonesia.